The Imperfect Panacea: American Faith in Education 1865-1990 - Perkinson, Henry J. (Toronto McGraw-Hill Inc., 1991)
The Imperfect Panacea. This brief text explains the changes and developments that have characterized American education history in terms of our attempts to use the schools to solve social, economic, and political problems.Focusing mainly on the post Civil War period, it shows how schools were used to help solve problems created by emancipation, urbanization, industrialization, and nationalization and how these attempts inevitably affected the organization, curriculum, and functioning of the school.
Keywords: Education